›China Bilder‹ Eine quantitative und qualitative Studie zu deutschsprachigen Publikationen mit China-Bezug und Übersetzungen chinesischsprachiger Originalwerke auf dem deutschen Buchmarkt 2006–2014 - Rautenberg, Ursula; Engl, Elisabeth; Qiu, Ruijing (2015)
The study aims at analysing images of China, as they are reflected in publications for the broad public on the German book market. It examines new German titles published between 2006 and 2014, which bear reference to China. On the basis of German translations of Chinese works and German originals about China, a thematic overview of the titles existing on the German book market is compiled. The concluding part examines the political, economic and cultural framework conditions, which affect the publication
BUCHWISS::pub-455

Gulangyu. Facetten einer Insel einst und jetzt (with collaboration of Dorothee Schaab-Hanke) - Lackner, Michael; Qiu, Ruijing (2023)

德国图书市场上的中国形象——与中国相关的德语出版物研究 - Rautenberg, Ursula; Engl, Elisabeth; Qiu, Ruijing (Publishing Science. Wuhan 23, 2015)
BUCHWISS::art-314